Combating Drug-Resistant Bacteria Using Photothermally Active Nanomaterials: A Perspective Review - Kaur, Kawaljeet; Reddy, Sagar; Barathe, Pramod; Shriram, Varsha; Anand, Uttpal; Proćków, Jarosław; Kumar, Vinay (Frontiers in Microbiology, 2021)
Injudicious use of antibiotics has been the main driver of severe bacterial non-susceptibility to commonly available antibiotics (known as drug resistance or antimicrobial resistance), a global threat to human health and healthcare. There is an upsurge in incidence of bacterial drug resistance not only in nosocomial but community settings as well, leading us to potentially ‘post-antibiotic era’. This threatening situation necessitates novel and effective strategies and nano-based approaches are gaining momentum. The exponential resurgence of multidrug resistant microorganisms and their unrivalled pathogenicity have broadened the photothermal therapeutic approaches for combating bacterial pathogens. Photothermally active nanomaterials (PANs) are broad-spectrum nanomaterials characterized by the heat energy conversion by d-d band transitions and surface plasmons with novel antibacterial applications via harnessing characteristics at the nanoscale. The thermal energy produced has the ability of antibacterial activity and bacterial inactivation via targeting the underlying drug resistance determinants. The current review capitalizes on the significance of using PANs that may be of considerable relevance in creating an effective approach for overcoming bacterial drug resistance. Various PANs leveraging broad-spectrum therapeutic antibacterial (both bactericidal and synergistic) potentials against drug-resistant pathogens have been discussed. The review also provides deeper mechanistic insights into the key action mechanisms of PANs against a variety of drug-resistant pathogens with a critical assessment on efflux pumps, cell membrane permeability, biofilm and quorum sensing inhibition. We also discuss the use of PANs as drug carriers. This review also deliberates about the possible cytotoxicities related with the therapeutic use of PANs and the effective strategies to overcome this. Recent developments, success stories, challenges, and prospects are also presented.